Mapping of acetabular posterior wall fractures using a three-dimensional virtual reconstruction software. Issue 6 (June 2021) - Cho, Jae-Woo; Cho, Won-Tae; Sakong, Seungyeob; Lim, Eic Ju; Choi, Wonseok; Kang, Seonghyun; Kim, Beom-Soo; Kim, Jin-Kak; Oh, Chang-Wug; Oh, Jong-Keon
Highlights: The fracture maps showed fracture pattern and recurrent fracture zone based on the articular and retro-acetabular surfaces. There is no remarkable pattern of marginal impaction. The new mapping technique can be useful and reproducible for analyzing other fractures that have complex 3D morphologies and patterns. Abstract: Introduction: The aim of this study was to analyze and describe the fracture patterns of the acetabular posterior wall based on quantitative measurements of the fracture characteristics. Materials and methods: Computed tomography images of 51 patients with acetabular posterior wall fractures from an initial cohort of 216 acetabular fractures were imported into a three-dimensional (3D) virtual software. The reconstructed 3D images were utilized to evaluate the following: (i) fracture line mapping on the inner articular and retro-acetabular surfaces, (ii) common zones of fracture and marginal impaction, and (iii) categorization by location and pattern of comminution. The clock-face position was applied for description: the midpoint of the transverse acetabular ligament served as the +180° reference point, and the 0° reference point was set perpendicular to the ligament. The fracture angle on the articular surface was defined as the intersection between the start and end points. The fracture span on the retro-acetabular surface was defined as the ratio of the perpendicular distance, which is between the fracture beak and acetabular rim, to the entire length, which is from the edge to the rim. Quantitative measurements were performed, and the fracture patterns were analyzed. A color scale bar was used to visualize the common and marginal impaction zones. Results: The articular surface mapping of all the cases demonstrated that the average starting point of the fracture line was +6.2° (±12.8°) and the endpoint was 96.7° (±13.3°), and the average fracture angle was 119.6° (±7.6°) with 80.6% of the fragments having angles within 18.7–117°. The retro-acetabular surface mapping demonstrated that the average fracture span was 0.65 ±0.20, and 61.7 % of the fracture lines were located within 0.6 to 0.9. Marginal impaction was found in 21 cases (21/51, 41.2%; range: between +7° and +105°). Conclusion: The fracture maps showed fracture patterns and recurrent fracture zones on the articular and retro-acetabular surfaces. However, there was no remarkable pattern of marginal impaction. Level of evidence: Retrospective cohort study